A ação supervisora das coordenadoras de serviços educacionais do município de Santo André - Selarin, Vânia Cristina (2016)
The main goal of this study is a general objective to characterize the supervising action of the the Coordenadoras de Serviços Educacionais (CSE) – Educational Services Coordinators – from the municipal educational system of Santo André – SP. The research problem was raised from the need for investigate the point of view of the Educational Services Coordinators on their supervisory action and on the knowledge they have on the assignments that are legally attributed to them in this function. This qualitative research uses the methodology of case study. The data was collected by Focus Groups: focus groups I and II and also by analysis of documents from Secretaria de Educação (SE) - Municipal Education Department - and legislation concerning the subject. The social subjects of the research were the Educational Services Coordinators (CSE) from the Departamento de Educação Infantil e Ensino Fundamental (DEIEF) – Department of Early Childhood Education and Elementary Education – of Santo André's Municipal Education Department. For the data analysis, the methodology of content analysis was used. The theoretical foundation of this research was referenced in studies of authors that deal with educational supervision as Alonso (2008), Alarcão (2015), Ferreira (2008, 2015), Lima (2015), Rangel (2008, 2015) and Saviani 2008). Also from the authors that deal with the coordination of teams such as Almeida and Placco (2009) and Placco and Gouveia (2013). Freire (1967, 1987, 2002, 2007) refers to discussions about reflection on practice; methodological rigor in supervisory action; ethics, esthetics and political action in the making of educational supervision. Romão (2010), subsidizes the discussion about education systems. The analysis of educational policies and public policies was referenced by Mainardes (2006) and Souza (2006). The mais results were organized in 7 (seven) distinct categories, based on the specialized literature, and they indicate that both groups of CSE analyzed have similar concepts and practice supervisory action of monitoring focusing specifically on the schools. The research also revealed that the CSEs are unaware of the duties that are legally instituted, and this lack of knowledge promotes concerns, possible overloads of work and misalignments. Conclusively, it was evidenced that the practice of supervised action of the researched, concentrates, essentially, on the fiscalizing, formative, articulating and transforming action, as essential roles to the function of educational supervision. Finally, this study allowed the characterization of the supervisory action of the Coordenadoras de Serviços Educacionais, and made clear the importance of their role in Santo André's educational system as well as helped identify the importance of actualizing this educational policy in order to ensure a good educational performance of the municipal education system.